The savvy investor's guide to building wealth through traditional investments - Baker, H. Kent; Nofsinger, John R., 1965-; Spieler, Andrew C. (The Savvy Investor's Guide, 2020)
Would you like to be a millionaire? While alternative investments are an option, this easy-to-read guide focuses on traditional investments - stocks, bonds, and cash or cash equivalents. Especially written for novice investors, if you want to become a millionaire and don't have the luck to buy a lottery ticket, this is the guide for you.